Enhanced nitrogen removal from electroplating tail wastewater through two-staged anoxic-oxic (A/O) process. (January 2018) - Yan, Xinmei; Zhu, Chunyan; Huang, Bin; Yan, Qun; Zhang, Guangsheng
Highlights: Two-staged A/O process was applied for depth treatment of electroplating tail wastewater. NH4 + -N and COD removal efficiencies reached 97.11% and 78.75%, respectively. Sludge from two aerobic reactors showed better resistance to high salinity shock. Both salt-tolerant and halophili bacteria were enriched in the combined process. Abstract: Consisted of anaerobic (ANA), anoxic-1 (AN1), aerobic-1 (AE1), anoxic-2 (AN2), aerobic-2 (AE2) reactors and sediment tank, the two-staged A/O process was applied for depth treatment of electroplating tail wastewater with high electrical conductivity and large amounts of ammonia nitrogen. It was found that the NH4 + -N and COD removal efficiencies reached 97.11% and 83.00%, respectively. Besides, the short-term salinity shock of the control, AE1 and AE2 indicated that AE1 and AE2 have better resistance to high salinity when the concentration of NaCl ranged from 1 to 10 g/L. Meanwhile, it was found through high-throughput sequencing that bacteria genus Nitrosomonas, Nitrospira and Thauera, which are capable of nitrogen removal, were enriched in the two-staged A/O process. Moreover, both salt-tolerant bacteria and halophili bacteria were also found in the combined process. Therefore, microbial community within the two-staged A/O process could be acclimated to high electrical conductivity, and adapted for electroplating tail wastewater treatment.